El comercio de la yuca fresca en los Departamentos de Atlantico, Bolivar, Cordoba y Sucre - Janssen, W. (International Center for Tropical Agriculture, 1984)
The results of a survey among 506 cassava middlemen (wholesalers and retailers) to investigate the rural and urban marketing structure for fresh cassava, in the departments of Atlantico, Bolivar, Cordoba, and Sucre (Colombia), are discussed. The course of fresh cassava from the farmer to the consumer is briefly described. Commercialization costs for fresh cassava are high due to perishability problems and uncertainty in demand, especially in urban centers. Although cassava has an attractive price in rural areas, its price in urban areas is too high compared with other crops (potato, plantain, yams). Research is being conducted on solving perishability factors in cassava, which cause most of the marketing problems. (CIAT)